Linear peptides from the venom of large marsh horsefly (Tabanus autumnalis) larvae facilitate prey capture and defense. - Dersch, L.; Bohlken, O.; Krämer, J.; Schulte, L.; Hardes, K.; Marner, M.; Schäberle, T.F.; Vilcinskas, A.; Lüddecke, T. (Insect Biochemistry and Molecular Biology, 2025)
Venoms are complex cocktails containing novel biomolecules. Many venomous animal groups are understudied, including Horseflies of the family Tabanidae. Their larvae utilize venom to overpower prey and to defend against predators. Recent studies uncovered short linear peptides in their venoms but their bioactivity spectrum and biological function remain unknown. Here, we employ a bioactivity profiling of eight synthesized toxins of the large marsh horsefly (Tabanus autumnalis) larval venom via in silico, in vitro, and in vivo experiments. Bioinformatic analysis suggest, that the selected peptides fold into cationic and amphipathic alpha-helices. Assays against microbes reveal antimicrobial activity potentially via membrane interaction caused by some of the linear Tabanus toxins, while tests on vertebrate cells reveal cytotoxic and hemolytic effects. Lastly, injections of the peptides in Drosophila melanogaster flies recovered insecticidal and paralytic activity. Based on our analysis, we propose that some of the linear T. autumnalis peptides facilitate prey capture via their rapid paralytic activity in insects. A second line of functional utilization may be present in defense against predators and microbial colonization. From a translational perspective, it appears unlikely that the tested peptides could efficiently be translated into anti-infectives, while an evaluation for agricultural exploitation demands further research. Our study provides functional insights into the toxin repertoire of one of the least studied venom systems on earth and serves as starting point to further investigate dipteran venom biology.